2017
DOI: 10.1080/14786419.2017.1350672
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from the leaves ofPinus dalatensisFerré

Abstract: A phytochemical study of n-hexane and ethyl acetate extracts of Pinus dalatensis Ferré leaves led to the isolation of 11 compounds, including one caryolane sesquiterpenoid (1), five labdane diterpenoids (2, 3, 4, 5, 6), one serratane triterpenoid (7), one diacylated flavonoid glucoside (8), one stilbenoid (9) and two sterols (10, 11). The structural characterisation of the isolated compounds was elucidated by spectroscopic data and comparison with the literature report on the chemical constituents from Pinus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…Compound 2 (Sa et al, ): Daucosterol: White powder, 1 H‐NMR (CDCl 3 ): δ 5.35 (1H, m, H‐6), 4.43 (1H, m, H‐3), 4.25 (1H, d, J = 6.0 Hz, H‐1′). 13 C‐NMR (CDCl 3 ): δ 38.5 (C‐1), 29.1(C‐2), 77.2 (C‐3), 39.6 (C‐4), 140.1 (C‐5), 121.3 (C‐6), 33.2 (C‐7), 31.1 (C‐8), 50.1 (C‐9), 25.9 (C‐10), 21.3 (C‐11), 28.5 (C‐12), 42.2 (C‐13), 56.8 (C‐14), 24.5 (C‐15), 42.3 (C‐16), 55.9 (C‐17), 12.3 (C‐18), 18.7 (C‐19), 36.5 (C‐20), 18.6 (C‐21), 36.0 (C‐22), 37.1 (C‐23), 45.7 (C‐24), 29.3 (C‐25), 18.2 (C‐26), 20.3 (C‐27), 23.3 (C‐28), 11.5 (C‐29), 101.0 (C‐1′), 73.5 (C‐2′), 77.56 (C‐3′), 70.2 (C‐4′), 78.8 (C‐5′), 61.7 (C‐6′).…”
Section: Methodsmentioning
confidence: 99%
“…Compound 2 (Sa et al, ): Daucosterol: White powder, 1 H‐NMR (CDCl 3 ): δ 5.35 (1H, m, H‐6), 4.43 (1H, m, H‐3), 4.25 (1H, d, J = 6.0 Hz, H‐1′). 13 C‐NMR (CDCl 3 ): δ 38.5 (C‐1), 29.1(C‐2), 77.2 (C‐3), 39.6 (C‐4), 140.1 (C‐5), 121.3 (C‐6), 33.2 (C‐7), 31.1 (C‐8), 50.1 (C‐9), 25.9 (C‐10), 21.3 (C‐11), 28.5 (C‐12), 42.2 (C‐13), 56.8 (C‐14), 24.5 (C‐15), 42.3 (C‐16), 55.9 (C‐17), 12.3 (C‐18), 18.7 (C‐19), 36.5 (C‐20), 18.6 (C‐21), 36.0 (C‐22), 37.1 (C‐23), 45.7 (C‐24), 29.3 (C‐25), 18.2 (C‐26), 20.3 (C‐27), 23.3 (C‐28), 11.5 (C‐29), 101.0 (C‐1′), 73.5 (C‐2′), 77.56 (C‐3′), 70.2 (C‐4′), 78.8 (C‐5′), 61.7 (C‐6′).…”
Section: Methodsmentioning
confidence: 99%
“…Pinus dalatensis and Pinus krempfii are endemic species in Vietnam, mainly distributed in Central Highlands Tay Nguyen, Vietnam. [1,3] Previous phytochemical studies of these plants lead to the isolation of diterpenes, sesquiterpenes, simple phenols, flavonoids, stilbenoids, lignans and other compounds. [1,2,3,4 ] Recent bioactivity experiments indicated that stilbenoid isolated from the leaves of P. dalatensis had cytotoxicity on SK-LU-1, MCF-7 and Hep-G2 cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…[1,3] Previous phytochemical studies of these plants lead to the isolation of diterpenes, sesquiterpenes, simple phenols, flavonoids, stilbenoids, lignans and other compounds. [1,2,3,4 ] Recent bioactivity experiments indicated that stilbenoid isolated from the leaves of P. dalatensis had cytotoxicity on SK-LU-1, MCF-7 and Hep-G2 cell lines. [1] Additionally, all the isolated compounds from P. dalatensis wood showed a selective anti-proliferative activity on leukaemic cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations